Dinâmica do emprego formal dos principais municípios do Rio Grande do Sul: uma análise estrutural-diferencial no período 2008-2018 - Cardoso, Pablo (2022)
The present study aimed to analyze, using the StructuralDifferential method, the dynamics of formal employment in the period between 2008 and 2018, in the main municipalities of Rio Grande do Sul, visàtwenty vis the dynamics between them in the Industry sectors, Commerce and Service. Specifically, we sought to: analyze the trajectory of employment in the municipal sphere among the twenty selected municipal ities in the sectors of Industry, Commerce and Service; identify dynamic municipalities in job creation, as well as those that lost the most jobs; use regional analysis coefficients to assist in data interpretation; make observations of the behavior of for mal employment in the 20082013 and 20132018 periods; compare the periods of analysis to identify whether growth occurred in the first five years as well as in the final five years. The structuraldifferential method (shift descshare) made it possible to ribe regional and sectoral expansion through the decomposition of its productive structure and thus to ascertain whether a region can present a higher growth rate than the average of a composite of regions. The data were all based on the Annual Report of S ocial Information (RAIS). As main results, it was found that for the twenty municipalities (B20) of Rio Grande do Sul, the industrial sector showed decreases of 13%, totaling the loss of 45,970 formal jobs in the tenyear period (2008 Analyzing the 2018). Total Net Variation (VTL), among the selected clippings, it was observed that the city of Porto Alegre obtained, for the three clippings, the worst performance, also highlighting, for the same clippings, the industrial sector as the least dynamic. Regardin g the allocation effect, in many municipalities, the changes were discrete. Considering the allocation effects, the Services sector was the one that presented stability in all the cuts.